Towards a solution of developing countries' debt crisis: Strengthening the weakest link - Peter König (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1989)
All current proposals and initiatives to a solution of the debt crisis of developing countries focus on the financial problems associated with the crisis, i.e. the level of external debt outstanding or the debt service payments, respectively. The link to the real sphere of the debtor countries is given via the adjustment programs surveyed by the International Monetary Fund (IMF) and the World Bank (IBRD). On the other hand, trade relations of and especially amongst the highly indebted countries have shown to be disrupted by the debt crisis. Establishing an International Fund for Trade Adjustment (IFTA) liable for stabilizing those trade flows instead of coordinating merely financial adjustments could provide an effective assistance in strengthening the economic performance of those countries with respect to their solvency.
Keywords: 330